Movement disorders that occurred as late manifestations of Alzheimer’s disease controlled by a low dose of carbamazepine - Patrick Manckoundia; Jérémie Vovelle; Sylvia Cancemi; Rachid Mahmoudi; Thomas Renoncourt (European Journal of Case Reports in Internal Medicine)
Introduction: According to the World Health Organization, 44 million people worldwide suffer from Alzheimer’s disease. Abnormal movements are atypical symptoms of Alzheimer’s disease. Case description: An 87-year-old woman, followed for Alzheimer’s disease, experienced abnormal movements. The episodes lasted 30 minutes, were involuntary, uncontrollable, anarchic, predominantly in the upper limbs, and without loss of consciousness or bladder control. An electroencephalogram ruled out atypical epilepsy. Pharmacovigilance investigation ruled out a drug-related cause. Magnetic resonance imaging revealed abnormalities suggestive of Alzheimer’s disease, with no other evidence to explain the abnormal movements. Apart from the presence of Alzheimer’s disease biomarkers, cerebrospinal fluid analysis found no abnormality. Dopamine transporter scan rule out an atypical parkinsonian syndrome. Finally, abnormal movements associated with Alzheimer’s disease were suspected. Abnormal movements disappeared within 72 hours on low-dose carbamazepine. Conclusion: This case is educational both because of the clinical presentation and the management of symptoms.